Short‐ and long‐term mortality after liver transplantation in patients with and without hepatocellular carcinoma in the UK. Issue 7 (3rd March 2020) - Wallace, D.; Cowling, T. E.; Walker, K.; Suddle, A.; Rowe, I.; Callaghan, C.; Gimson, A.; Bernal, W.; Heaton, N.; van der Meulen, J.
Abstract : Background: The increasing demand for liver transplantation has led to considerable changes in characteristics of donors and recipients. This study evaluated the short‐ and long‐term mortality of recipients with and without hepatocellular carcinoma (HCC) in the UK between 1997 and 2016. Methods: First‐time elective adult liver transplant recipients in the UK were identified and four successive eras of transplantation were compared. Hazard ratios (HRs) comparing the impact of era on short‐term (first 90 days) and longer‐term (from 90 days to 5 years) mortality were estimated, with adjustment for recipient and donor characteristics. Results: Some 1879 recipients with and 7661 without HCC were included. There was an increase in use of organs donated after circulatory death (DCD), from 0 per cent in era 1 to 35·2 per cent in era 4 for recipients with HCC, and from 0·2 to 24·1 per cent for non‐HCC recipients. The 3‐year mortality rate decreased from 28·3 per cent in era 1 to 16·9 per cent in era 4 (adjusted HR 0·47, 95 per cent c.i. 0·35 to 0·63) for recipients with HCC, and from 20·4 to 9·3 per cent (adjusted HR 0·44, 0·36 to 0·53) for those without HCC. Comparing era 4 with era 1, improvements were more marked in short‐term than in long‐term mortality, both for recipients with HCC (0–90 days: adjusted HR 0·20, 0·10 to 0·39; 90 days to 5 years: adjusted HR 0·52, 0·35 to 0·75; P = 0·043) and for non‐HCC recipients (0–90 days: adjusted HR 0·32, 0·24 to 0·42; 90 days to 5 years: adjusted HR 0·52, 0·40 to 0·67; P = 0·024). Conclusion: In the past 20 years, the mortality rate after liver transplantation has more than halved, despite increasing use of DCD donors. Improvements in overall survival can be explained by decreases in short‐term and longer‐term mortality. Abstract : The increasing demand for liver transplantation has led to considerable changes in the characteristics of donors and recipients in the UK. However, in the past 20 years, mortality after liver transplantation has more than halved, despite increasing use of livers donated after circulatory death. HCC, hepatocellular carcinoma. More than halved in recent years Abstract : Antecedentes: La creciente demanda de trasplante hepático ha determinado cambios considerables en las características de los donantes y receptores. En este estudio, se evaluó la mortalidad a corto y a largo plazo de los receptores de trasplante hepático por carcinoma hepatocelular ( hepatocelular carcinoma, HCC) y no‐HCC en el Reino Unido entre 1997 y 2016. Métodos: Se identificaron los receptores adultos de un primer trasplante hepático electivo en el Reino Unido y se compararon cuatro eras sucesivas de trasplante. Se estimaron los cocientes de riesgos instantáneos ajustados ( adjusted hazard ratio, aHR) que comparaban el impacto de la era en la mortalidad a corto plazo (primeros 90 días) y a largo plazo (de 90 días a 5 años) ajustando por las características del receptor y del donante. Resultados: Se incluyeron 1.879 receptores HCC y 7.661 receptores no‐HCC. Hubo un aumento en el uso de donantes después de parada cardíaca ( donors following circulatory deat h, DCD) del 0% en la era 1 al 35, 2% en la era 4 para los receptores HCC y del 0, 2% al 24, 1% para los receptores no‐HCC. La mortalidad a los 3 años disminuyó de 28, 3% en la era 1 a 16, 9% en la era 4 (aHR 0, 47, i.c. del 95% 0, 35‐0, 63) para receptores HCC y de 20, 4% a 9, 3% (aHR 0, 44, 0, 36‐0, 53) para receptores no‐HCC. Comparando la era 1 y la era 4, las mejoras en la mortalidad a corto plazo fueron más marcadas que en la mortalidad a largo plazo, tanto para receptores HCC (aHR 0‐90 días 0, 20, 0, 10‐0, 39; 90 días‐5 años 0, 52, 0, 35‐0, 75; P =舁0, 04) como para receptores no‐HCC (aHR 0‐90 días 0, 32, 0, 24‐0, 42; 90 días‐5 años 0, 52, 0, 40‐0, 67; P =舁0, 02). Conclusión: En los últimos 20 años, la mortalidad después del trasplante de hígado se ha reducido a más de la mitad, a pesar del uso cada vez mayor de donantes DCD. Las mejoras en la supervivencia global pueden explicarse por la disminución de la mortalidad a corto y largo plazo.